Assessment of Coverage in England of Cancer Drugs Qualifying for US Food and Drug Administration Accelerated Approval - Cherla, Avi; Naci, Huseyin; Kesselheim, Aaron S; Gyawali, Bishal; Mossialos, Elias (JAMA internal medicine, 2021)
Numerous cancer drugs have received accelerated approval from the US Food and Drug Administration (FDA) based on clinical trial outcomes that are otherwise not acceptable for traditional FDA approval; the accelerated approval process allows outcomes based on surrogate measures that are only reasonably likely to estimate clinical benefits. In England, the National Institute for Health and Care Excellence (NICE) evaluates the clinical benefits and cost-effectiveness of drugs after they have received regulatory approval and issues recommendations regarding their coverage in the National Health Service (NHS). However, the level of concordance between European and FDA decision-making in the context of drugs qualifying for FDA accelerated approval is unknown. To compare FDA accelerated approval decisions for cancer drugs with NICE coverage decisions. This retrospective cohort study compared cancer drug indications that received FDA accelerated approval from December 11, 1992, to May 31, 2017, with the same set of drug indication pairs in England until August 31, 2019. Data from European Public Assessment Reports developed by the European Medicines Agency (EMA) and public appraisal documents from NICE were used to determine NHS coverage recommendations. National Institute for Health and Care Excellence (NICE) public appraisal documents were analyzed for drug indications, characteristics of clinical evidence, cost-effectiveness, and coverage decisions. Data were analyzed from September 1 to December 31, 2019. Cancer drug indication coverage decision by NICE. From 1992 to 2017, 93 cancer drug indications received FDA accelerated approval, 6 of which were subsequently withdrawn, leaving 87 cancer drug indications on the market. As of August 2019, 5 of these indications had been withdrawn or denied market authorization for the European Union by the EMA. From the cohort of EMA-approved drugs, an additional 7 drug indications were not recommended by NICE and were not deemed to have sufficient clinical benefits or cost-effectiveness to warrant mandatory public coverage in England; 5 drugs were not recommended based on clinical benefit and cost-effectiveness criteria, and 2 drugs were not recommended based on cost-effectiveness criteria alone. In total, 12 drug indications were not recommended for public coverage in the NHS, and an additional 30 drug indications were not reviewed by either the EMA (14 drug indications) or NICE (16 drug indications) by the study end date. Most drug indications recommended by NICE were conditional on the negotiation of additional confidential discounts, the imposition of restricted indications that limited prescribing to specific patient subgroups, or the collection of additional data. Among the 9 drug indications with evidence of overall survival benefit at the time of NICE review, 2 were not recommended for public funding based on cost-effectiveness criteria. In this cohort study, 30 cancer drug indications that were granted accelerated approval by the FDA were not subsequently reviewed by either European regulators or NICE, and 12 drugs were denied authorization or coverage owing to insufficient safety, clinical efficacy, or cost-effectiveness. National Health Service coverage of cancer drugs given FDA accelerated approval commonly required additional price concessions, restrictions to approved indications, or review of additional data.